Effect of Knowledge Management and Learning Orientation on Process Innovation in Mitra Group - Nugraheni, Putriana Alya; Kurniani, Kurniani - (Politeknik Negeri Semarang, 2023)
This study is about human resource management which aims to analyze the effect of knowledge management and learning orientation as independent variables on process innovation as the dependent variable, either partially or simultaneously. The population in this study are the employee of Mitra Group, with 42 respondents who are selected using a census sampling technique as the sample. The data used in this study is primary data obtained through the distribution of questionnaires. This research is in line with research on knowledge management conducted by du Plessis (2007), Al-Sa”™di et al. (2017), and learning orientation by Zayed & Alawad (2017). The data analysis method starts from the validity test, reliability test, and continues with the classical assumption test which is processed using the Statistical Package for the Social Sciences (SPSS) version 25. The results of this study indicate that simultaneously and significantly all independent variables have an effect on the dependent variable seen from the results of the simultaneous significance test (F test) with a significance of 0,003 which is worth less than the standard significance of 0,025. The results of the partial significance test (t test) on the knowledge management variable on process innovation have a significant result of 0,002, while the learning orientation variable on process innovation has a non-significant result of 0,922. The result of the coefficient of determination (R2) shows that 25,2% of innovation is influenced by independent variables in this study, and 74,8% is influenced by other factors. The result of multiple linear regression analysis is Y= 1,194 + 0,638X1 + 0,022X2 which shows the positive equation of knowledge management and learning orientation on process innovation.